Vehicle Detection and Recognition for Allowing into Premises Using OCR - U, Nadhiya; K, Mahalakshmi; P, Kaviyarasu (Journal of Ubiquitous Computing and Communication Technologies, 2023)
The research has proposed a system to automatically detect the number plate and recognize it using optical character recognition method. Before taking a image of the number plate, the developed system first recognizes the car. Image segmentation is used to recover the portion of an image that contains the vehicle identification number. Character recognition is accomplished using an optical character recognition technique. This involves using matching techniques to check whether the car plate image matches the data in the database. The warning sign will show when authenticity is verified, and the car will then be permitted to enter the designated area. Real-time video is captured to evaluate the system’s functionality, and Python is used to create and simulate the system. Due to its promising nature the suggested method is employed in the automated vehicle authentication in universities in future.